Targeting mitochondrial metabolites and nucleic acids as an anti-inflammatory strategy - Min, Yukun; O’Neill, Luke A. J. (Frontiers in Drug Discovery, 2023)
Mitochondrial metabolites and their derivatives have been the focus of recent efforts to develop new anti-inflammatory therapeutics. The widely used therapeutic agents dimethyl fumarate (DMF) and metformin have anti-inflammatory properties and have been shown to target metabolism. The mitochondrial metabolites succinate, itaconate, and fumarate have multiple immunomodulatory effects and present interesting therapeutic possibilities for immune and inflammatory diseases. Mitochondrial DNA and double-stranded RNA have also been shown to be highly inflammatory, acting via specific pattern recognition receptors (PRRs) such as cGAS and TLR9 for mitochondrial DNA, RIG-I, MDA5 for mitochondrial double stranded RNA, and TLR7 for mitochondrial single stranded RNA. These recent discoveries are changing our view of mitochondria suggesting that they are at the heart of multiple inflammatory diseases and provide opportunities for the development of new anti-inflammatory therapeutics.